ANALYSIS OF THE IMPLEMENTATION OF APPROPRIATE TECHNOLOGY TO SUPPORT COMMUNITY BUSINESS PRODUCTIVITY IN SIMPANG AGUNG VILLAGE, SEPUTIH AGUNG DISTRICT, CENTRAL LAMPUNG REGENCY - Lidia Eva Sari; Malik (International Journal of Multidisciplinary Reseach, 2026)
The research method used is descriptive qualitative research. This method is used to describe the analysis of the application of appropriate technology to support community business productivity in Seputih Agung Village, Seputih Agung District, Central Lampung Regency. All data were obtained directly from informants in the field using interviews and document studies. The research results show that (1) the implementation of Appropriate Technology in Simpang Agung Village, Seputih Agung District, Central Lampung Regency, according to the dimensions of (a) Compatibility, (b) Ease of Use (Simplicity/Complexity), (c) Efficiency and Productivity, (d) Affordability/ Accessibility, (e) Sustainability, and (f) Empowerment, has generally made a positive contribution to supporting community business productivity. The use of TTG can help business actors improve work efficiency, accelerate production processes, and improve product yields and quality compared to traditional methods. Furthermore, appropriate technology also plays a role in encouraging business independence, improving community skills, and opening up opportunities for increasing income based on local potential. (2) Aspects inhibiting the effectiveness of appropriate technology implementation have not been fully optimized because several obstacles still affect the sustainability and expansion of its use. These obstacles relate to the suitability of the technology to local needs, limited technical capabilities of users, affordability, and minimal ongoing mentoring.